An unusual ischaemic presentation of thrombosed intracranial mycotic aneurysm with subsequent subarachnoid haemorrhage. Issue 10 (10th October 2020) - Brown, Patrick; Fulks, Daniel
Abstract : We present an unusual case of acute ischaemic stroke secondary to thrombosed mycotic aneurysm with subsequent early aneurysmal rupture and subarachnoid haemorrhage, successfully treated with endovascular coil embolisation of the thrombosed segment. Imaging correlates are presented demonstrating successful endovascular management despite vessel occlusion precluding angiographic visualisation of the aneurysmal segment. Imaging and clinical follow-up is provided demonstrating durable occlusion and excellent clinical outcome with full functional recovery.